Adjuvant intensity-modulated radiotherapy (IMRT) with concurrent paclitaxel and cisplatin in cervical cancer patients with high risk factors: A phase II trial. Issue 8 (August 2015) - Wang, X.; Shen, Y.; Zhao, Y.; Li, Z.; Gou, H.; Cao, D.; Yang, Y.; Qiu, M.; Li, Q.; Liu, J.; Yi, C.; Liao, Z.; et al.
Abstract Objective To evaluate the safety and efficacy of adjuvant intensity-modulated radiotherapy (IMRT) with concurrent paclitaxel and cisplatin (TP) in early stage cervical cancer patients with high risk factors after radical hysterectomy. Methods Patients who underwent radical hysterectomy for FIGO stage IB–IIA cervical cancer and had high risk factors for recurrence were recruited. One cycle of TP was delivered before and after concurrent chemoradiotherapy, respectively. Concurrent chemoradiotherapy began 21 days after the start of the initial cycle of the chemotherapy with two cycles of TP delivered on day 1 and day 29 of radiotherapy. Primary endpoints were overall survival (OS) and relapse-free survival (RFS), with toxicities, local-regional control (LC) and distant failure (DF) rate as secondary endpoints. Results Between 2008 and 2012, 67 patients were evaluable. The 2 and 4-year RFS rates were 98.2% and 92.9%. Corresponding OS rates were 100%, and 98.0%, respectively. The 4-year LC and DF rates were 98.0% and 5.2%, respectively. Grade 3–4 acute leucopenia, neutropenia and thrombocytopenia occurred in 25.4%, 11.9% and 1.5% of patients, respectively. There were 89.6% and 59.7% patients experienced acute vomiting and diarrhea, but only 6.0% and 6.0% patients were grade 3, respectively. No case of chronic toxicity exceeded grade 2. Conclusion Adjuvant concurrent IMRT with paclitaxel plus cisplatin are safe and effective in early stage cervical cancer patients with high risk factors for recurrence following radical hysterectomy.